2012
DOI: 10.1002/adfm.201200564
|View full text |Cite
|
Sign up to set email alerts
|

Using Directed Self Assembly of Block Copolymer Nanostructures to Modulate Nanoscale Surface Roughness: Towards a Novel Lithographic Process

Abstract: Nanoscale surface roughness is an important factor in determining the properties of surfaces and can affect the performance of a range of devices prepared by lithographic methods. Here, a method is reported, which enables modulation of the nanoscale roughness of surfaces through the directed self assembly (DSA) of positively charged polymersomes, composed of specifically designed block copolymers, onto negatively charged surfaces. Assembly of the polymersomes on surfaces can result in an increase in the nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…26,27 Continuous efforts have been devoted to explore the versatility of this photo-induced technique over acrylate monomers, including solketal acrylate, hydroxyethyl acrylate and glycidyl acrylate homopolymer, or even poly(methyl acrylate)-b-poly(solketal acrylate). 40,41 Many of these applications require polymers to self-assemble into specific conformations. 29,30 Followed by hydrolysis of the tert-butyl group to the hydroxyl group the resulting decablock copolymer has shown a complex thermo and pH-responsive self-assembled behavior.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Continuous efforts have been devoted to explore the versatility of this photo-induced technique over acrylate monomers, including solketal acrylate, hydroxyethyl acrylate and glycidyl acrylate homopolymer, or even poly(methyl acrylate)-b-poly(solketal acrylate). 40,41 Many of these applications require polymers to self-assemble into specific conformations. 29,30 Followed by hydrolysis of the tert-butyl group to the hydroxyl group the resulting decablock copolymer has shown a complex thermo and pH-responsive self-assembled behavior.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 On the other hand, graphoepitaxy uses surface topography, e.g., a printed resist, to guide self-assembly and align the phase-separated domains. [16][17][18][19][20] Polystyrene-block-poly(methyl methacrylate), or PS-b-PMMA, is currently the most widely studied system, where DSA of PS lines with a pitch of ∼24 nm has been demonstrated. 21 There is also a significant body of knowledge relating to optimization of processing and integration with manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-TEM of the aqueous solutions revealed that polymersomes had formed with a diameter of 18 ± 2 nm. [47] This is represented schematically in Figure 2 A. ,J 3 . K`: _ ie',«9r i. a flat surface or (C) a rough surface.…”
Section: Solution Properties Of the Block Copolymer And Adhesion To Pmentioning
confidence: 99%